[Refrain] : Alexa Illi Master of Fine Arts thesis - Illi, Alexa (My University, 2025)
Before students in the Master of Fine Arts program in the Academy of Fine Arts graduate, they are required to execute a project that consists of an artistic component and a written component, in the scope of fourty credit points. The artistic component is to be an artwork, performance or other artistic endeavour alongside a public presentation of such. The written component is to be a piece of writing – no more than thirty pages long – that gives further context to the artistic component. It can also be thought of as a companion piece to the artwork. In this written component of my Master of Fine Arts thesis project I will present the artistic component — a spatial installation entitled [Refrain], consisting of photographic prints, textile and various objects in the sixth floor — the very top space — of the academy. This space is currently known as Majakka – meaning Lighthouse. It is a former grain silo. The key — as in most notable upon first glance — elements of the artwork are a large-scale inkjet print in three parts depicting the artist on her bed in her bedroom and an overlong curtain over a window taped with perforated window tape. The work — as in artistic component — was exhibited at the Kuvan Kevät 2025 exhibition at the Academy of Fine Arts’ Sörnäinen campus from 19 May til 15 June 2025. In written form I will go through certain events and affects that informed my thinking during this process and more broadly as an artist before and after. Some of these writings are more directly linked to the visual composition of the artwork, while others have less to do with the visual language of my artistic practice but rather speak to a certain philosophy or sensibility I deem important, but might – to a new reader – read as erratic, or unrelated or disjointed. I like it that way. There has always been an element of elaborateness to my process that has taken time for me to fully grasp and justify, that now inhabits the very core of my art. The (sub)textual facet is of the essence. This is something I cherish. The devil is in the detail. And familiarity breeds contempt.
Keywords: spatial installation; Installation (art); opinnäytteet; maisterit; fi=tila-aikataiteet|sv=tid- och rumkonst|en=Time and Space Arts|